Siphonophore genome structure and the evolution of functional specialization - Namrata Ahuja; Darrin T. Schultz; Dalila Destanović; Samuel H. Church; Natasha Picciani; Catriona Munro; Koto Kon-Nanjo; Tetsuo Kon; Maciej K. Mańko; Wendy Shi; Oleg Simakov; Casey W. Dunn (PLoS ONE, 2026)
Siphonophores (Cnidaria: Hydrozoa) are pelagic colonial marine invertebrates with many highly specialized bodies (zooids) within a single colony. Their unique biology and ecological importance have made them of particular interest, and motivate questions on their genomic structure, organization and content. To investigate siphonophores’ genome biology and develop resources for future studies, we sequenced the genome of a single Nanomia septata to chromosome scale. The haploid genome is 1.7 GB across 8 chromosomes. Relative to closely related hydrozoan genomes, this is an expansion in length but a reduction, from 15, in chromosome number, indicating multiple chromosomal fusion events. We found no genomic features clearly associated with siphonophores’ exceptional colony-level complexity. Gene families that play critical roles in cnidarian development have not expanded, and gene proximity was not generally correlated to their expression across zooids, except in male gonophores. To contextualize these observations, we sequenced 20 additional Nanomia specimens across the globe and mapped them to our chromosome-scale reference. Population genomic analyses support three previously recognized species of Nanomia , and at least one additional undescribed species. Present day overlapping geographic distribution of some Nanomia species raises the possibility of reproductive isolation in sympatry. Phylogenetic analyses of genome size indicate Nanomia septata and Nanomia cara have similarly large genomes around 1.7 GB, while Nanomia bijuga and an undescribed species show a secondary reduction to 0.7 GB. These results highlight how genomic factors have shaped colony organization and genome diversity within Nanomia.